Trending Speculations of Tumor-Initiating Cells in Squamous Cell Cancers of Head and Neck - Kamate, Wasim (Int J Stem Cells, 2017)
Tumor-initiating cells are a diminutive subpopulation of stem cells that have ability of long term self-renewal and generation of varied traits of tumor cell population. Understanding the concept of tumor-initiating cells may have a great implicative intimation for our comprehension of cancer pathobiology and for the delineation of new therapies directed towards these stem cells. The present review is an endeavor to conceptualize the role of tumor-initiating cells in the Squamous Cell Cancers (SCC) of head and neck, their role in tumorigenesis and the possible supplementary approach in the latest treatment modalities.